Decree-Law Of The President Of The Arab Republic Of Egypt No. 117 Of The Year 2015 On Amending Certain Provisions of the Social Insurance Law promulgated by law No. 79 of the year 1975 = قرار رئيس جمهورية مصر العربية بالقانون رقم 117 لسنة 2015 بتعديل بعض أحكام قوانين التأمين الإجتماعى الصادر بالقانون رقم 79 لسنة 1975 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic